Compositional, Structural, and Optical Characterizations of In1-XGaxN Epilayers Grown by High Pressure Chemical Vapor Deposition - Acharya, Ananta R.; Thoms, Brian D. (Himalayan Physics, 2012)
The compositional, structural and optical characterizations of In1-xGaxN epilayers grown by high pressure chemical vapor deposition have been carried out using Auger electron spectroscopy, x-ray diffraction and optical transmission spectroscopy. Auger electron spectroscopy revealed 14% gallium and 86% indium composition of the total metal contents in the In1-xGaxN epilayers. X-ray diffraction pattern showed three prominent peaks centered at 31.4?, 32.86? and 34.5? which are assigned to In1-xGaxN (0002), In (101) and GaN (0002) Bragg reflexes respectively. These results indicate no macroscopic observable phase separation in the analyzed In1-xGaxN sample. The optical transmission spectroscopy and the Beer-Lambert’s law quatified the absorption band edge to be 1.6 eV for the analyzed In1-xGaxN epilayers. The Himalayan Physics Vol. 3, No. 3 2012 Page: 6-9